Cross-reactivity between Coxiella burnetii and chlamydiae - Lukácová, M; Melnicáková, J; Kazár, J (Folia microbiologica, 1999)
A cross-reactivity among some strains of Coxiella burnetii and chlamydiae with immune rabbit and mouse sera in ELISA and immunoblot analysis was observed. In the latter, the cross-reactivity disappeared after a treatment of C. burnetii or C. psittaci with proteinase K, which indicates that only proteins were involved. The observed cross-reactivity was not influenced by host chick embryo yolk sac proteins. After adsorption of immune rabbit sera with homologous corpuscular antigens the cross-reactivity disappeared. The possibility of influence of such cross-reactivity on serological diagnosis of C. burnetii or chlamydiae infections is discussed.
Keywords: imunoblotting; zkřížené reakce; Antigens, Bacterial; Coxiella burnetii; Immune Sera; Q-horečka; antisérum; chlamydiové infekce; Female; ELISA; antigeny bakteriální; myši inbrední BALB C; Cross Reactions; zvířata; myši; Chlamydia; Enzyme-Linked Immunosorbent Assay; Mice; ženské pohlaví; Rabbits; králíci; Immunoblotting; Animals; Q Fever; Chlamydia Infections; Mice, Inbred BALB C